Cubic GaN/AlN multi‐quantum wells grown on pre‐patterned 3C‐SiC/Si (001). Issue 2 (20th January 2014) - Kemper, R. M.; Mietze, C.; Hiller, L.; Stauden, T.; Pezoldt, J.; Meertens, D.; Luysberg, M.; As, D. J.; Lindner, J. K. N.
Abstract We report for the first time on the growth of cubic AlN/GaN multi‐quantum wells (MQWs) on pre‐patterned 3C‐SiC/Si (001) substrates. The sample structure consists of 10 periods of 2 nm c‐AlN barriers with a 4 nm c‐GaN layer in between, which were grown on 3C‐SiC post shaped structures by means of molecular beam epitaxy. Substrate patterning has been realized by electron beam lithography and a reactive ion etching process. The 3C‐SiC posts have a length of about 550 nm and a height of about 700 nm. (Scanning) transmission electron microscopy studies show that the morphology of the MQWs is clearly influenced by 111 stacking faults, modulating the local growth rate. Further, the growth at the edges of the surface pattern is investigated. The MQW layers cover the 90° edges by developing low‐index facets rather than by forming a conformal system of 90° angled layers. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)